METHODS OF INCREASING THE LEVEL OF COMPETITIVENESS OF THE RUSSIAN FEDERATION IN THE WORLD THROUGH SUSTAINABLE DEVELOPMENT OF HUMAN CAPITAL - E. S. Novikova (Вестник университета)
The methods of increasing the level of competitiveness of the Russian Federation in the world through sustainable development of human capital have been studied. The analysis of the most considerable indicators in the social and economic development of Russia and other leading economies in order to understand the current place and role of the Russian economy in the world society has been presented. Based on the analysis a number of reasons influencing on the further development of the Russian economy, taking into account the more active use of human capital in the global structure of the economy, has been revealed. The result of the study was to identify the weakest issues of the Russian economic structure including the fundamental difficulties in the development of human capital. At the end of the article, the main recommendations for fixing the identified problems have been given.